Correlation between serological biomarkers of extracellular matrix turnover and lung fibrosis and pulmonary artery hypertension in patients with systemic sclerosis. (5th February 2020) - Kubo, Satoshi; Siebuhr, Anne Sofie; Bay‐Jensen, Anne‐C.; Juhl, Pernille; Karsdal, Morten A.; Satoh, Yurie; Todoroki, Yasuyuki; Nakano, Kazuhisa; Nakayamada, Shingo; Tanaka, Yoshiya
Abstract: Objective: To determine the value of serological biomarkers of collagen degradation/turnover as serum markers of organ involvement in patients with systemic sclerosis (SSc). Methods: Serum samples were obtained from 79 SSc patients and 19 healthy control subjects. Types I to VI collagen turnover, excluding type II collagen, were evaluated using nine serological biomarkers. Organ involvement, such as interstitial lung disease (ILD), pulmonary arterial hypertension (PAH), esophageal motility disorder, lower gastrointestinal lesions, joint contractures and digital ulceration, were evaluated and correlated with serum biomarkers. Results: Among multiple serological biomarkers of collagen turnover, the mean level of C5M was higher in SSc (3.9 ng/mL) than healthy subjects (2.6 ng/mL). In addition, PRO‐C6 (12.6 ng/mL vs 5.4 ng/mL) and C6M (26.0 ng/mL vs 16.7 ng/mL) were higher in SSc than the controls. The modified Rodnan skin score correlated with PRO‐C3 and PRO‐C6. Serum level of C6M was higher in patients with ILD. Furthermore, serum levels of PRO‐C3, PRO‐C6, and C6M were higher in patients with PAH. The use of high levels of these biomarkers as risk factors of PAH showed that all patients with PAH had high levels of risk factors. Of note, two‐third of patients with serum PRO‐C3, PRO‐C6 and C6M values above the respective cut‐off values had PAH. Conclusion: Our study indicated that collagen turnover abnormality, especially type VI collagen, is not only important pathologically in skin sclerosis but also in organ involvement. These biomarkers of collagen turnover are potentially clinically useful as biomarkers of organ involvement in SSc.